RECENT DATA ON TYPE 1 DIABETES MELLITUS IN CHILDREN - Dan Moraru; Evelina Moraru; Carmen Oltean; Laura Bozomitu; Bogdan A. Stana (Amaltea Medical Publishing House, 2008)
The paper reviews present and principal aspects of type 1 diabetes mellitus in children. There are presented: epidemiology of type 1 diabetes mellitus, with important geographical variations that the magnitude of the problem, main etiopathogenical aspects (genetical, immunological, environmental), etiologic classification of diabetes according to ISPAD 2000 Guidelines with main disease mechanisms and clinical features in children. The authors also discuss laboratory diagnosis and complex therapy of diabetes, which lies on the therapeutic triad: insulin therapy with available products, diet and exercise along with pacient education and self-monitoring. There are also mentioned acute and chronic complications, autoimmune associated diseases, legal matters and prognosis of this disease with immune pathogenic features in focus.